2005
DOI: 10.1093/humrep/deh663
|View full text |Cite
|
Sign up to set email alerts
|

Expected poor responders on the basis of an antral follicle count do not benefit from a higher starting dose of gonadotrophins in IVF treatment: a randomized controlled trial*

Abstract: Expected poor response patients, defined as patients with an AFC <5, are likely not to benefit from a higher starting dose of gonadotrophins in IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(118 citation statements)
references
References 41 publications
5
105
0
8
Order By: Relevance
“…This was proven by the negative association of the starting rhFSH dose with the number of oocytes collected, being the highest doses used in patients with a poor prognosis. Our data is consistent with those of two randomized trials [39,40].…”
Section: Discussionsupporting
confidence: 92%
“…This was proven by the negative association of the starting rhFSH dose with the number of oocytes collected, being the highest doses used in patients with a poor prognosis. Our data is consistent with those of two randomized trials [39,40].…”
Section: Discussionsupporting
confidence: 92%
“…Another study which compared the number of retrieved oocytes and IVF cancellation rates in previous poor responders found absolutely no benefit from increasing the starting dose of FSH above 150 IU/day [4]. Furthermore, predicted poor responders, based on either marginally elevated levels of basal FSH [23] or low antral follicle count [34], were not shown to benefit from an increase in starting dose of FSH. In support of this theory is the recent publication by Pal et al [35] who have described a reduced likelihood of clinical pregnancy and live birth and a trend towards a higher likelihood of miscarriage with the use of high dosages of gonadotrophin.…”
Section: Discussionmentioning
confidence: 99%
“…There is only one randomised controlled trial that looked at the efficacy of doubling the starting dose in women who are anticipated to respond poorly [19]. Those patients with <5 antral follicles just prior to starting gonadotrophins were recruited for the study.…”
Section: Expected Poor Respondersmentioning
confidence: 99%
“…As mentioned previously, the RCTs by Out et al [14] and Yong et al [15] elegantly demonstrated that higher starting doses of FSH in normal responders do not result in more eggs once they are over the age of 33 years. Similarly, expected poor responders experienced no benefit from being started on a dose of 300 IU instead of 150 IU [19]. If they do not already do so in the first cycle, it seems irrational to expect older women to respond better to a higher dose in a subsequent cycle.…”
Section: Dose Following a Poor Responsementioning
confidence: 99%